The Surgical and conservative treatment of pectus excavatum - Ejsner, Rafal; Barczyńska , Katarzyna; Grelowska, Aleksandra; Oto, Aleksandra; Ołubiec, Adrian; Sys, Tomasz; Gloc, Ewa; Bilińska, Aleksandra; Dmowska, Dominika; Błażuk, Michał; et al. (Quality in Sport, 2026)
Pectus excavatum is one of the most common chest defect in children. It is characterized by a collapsed sternum, reduced thoracic volume and cardiovascular and respiratory symptoms. In order to determine the degree of deformation and its type, diagnostic management is necessary, including imaging tests such as CT scans, from which the degree and nature of the defect can be determined, as well as other tests to determine the impact of the defect on the patient’s functioning. Treatment options include non-invasive methods and invasive methods such as the minimally invasive Nuss procedure or Ravitch procedure. The gold standard of treatment is the Nuss procedure, but in some cases, conservative treatment may be an alternative. Each method has its advantages and disadvantages, and the treatment method is selected after talking to the patient, determining his expectations, age, severity of the defect and its nature.